The Association between Resolvin D1 Levels and Gestational Diabetes Mellitus: Implications for Perinatal Outcomes - Zeynep Seyhanli; Burak Bayraktar; Mevlut Bucak; Gulsan Karabay; Betul Tokgoz Cakir; Can Ozan Ulusoy; Gizem Aktemur; Selver Ozge Sefik; Serap Topkara Sucu; Sevki Celen; Ali Turhan Caglar (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: To evaluate maternal Resolvin D1 levels in women with gestational diabetes mellitus (GDM) and investigate the association between perinatal outcomes.